Swot Analysis Of Small And Medium Micro Business Development In Jatiuwung District, Tangerang City - Rinintha Parameswari; Diana Silaswara; Andy Andy (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study is to determine how the development of MSMEs in Jatiuwung sub-district, Tangerang City, where there are Tangerang specialties and souvenirs that are commonly consumed by the general public. Where this analysis uses SWOT and describes it in the SWOT matrix.Based on the research results, the potential for development in the products of Micro, Small and Medium Enterprises is quite good in terms of organization, products, and others. And also for Micro, Small and Medium Enterprises, Jatiuwung has a team that supports each other and this needs to be maintained and improved. For the product itself, it is very good in terms of taste and packaging to be able to increase sales, quality improvement and other creative ideas are needed. In the promotion itself, it has been through social media which is often used through WA and there is a need for an increase to the market place, and no less important is the support from the Regional Government who has provided a place at the Jatiuwung District Office and this greatly helps the marketing process to the community directly.